2023
DOI: 10.1002/cam4.5909
|View full text |Cite
|
Sign up to set email alerts
|

Multiperspective quantitative tumor–stroma ratio reveals histological areas associated with poor outcomes in oral squamous cell carcinoma

Abstract: Aims Different regions of oral squamous cell carcinoma (OSCC) have particular histopathological characteristics, and the individual histological characteristics of the tumors are poorly understood. Therefore, calculating the proportion of tumor cells in different regions that allow assessment of the prognostic outcomes for OSCC patients would be of great clinical significance. Methods and Results We established an open‐source software‐based analytic pipeline that defines the inner tumor and invasive tumor fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Thus, appropriate prediction and risk stratification (based on multiple prognostic factors) is essential toward a better treatment planning of NPC. The significance of TSR has been studied in different types of epithelial malignancies including oral squamous cell carcinoma, 16 triple-negative breast cancer, 6 non–small cell lung cancer, 17 and urothelial carcinoma 7 . In NPC, one previous study has reported the significance of TSR based on a single institution cohort from an endemic region (China) 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, appropriate prediction and risk stratification (based on multiple prognostic factors) is essential toward a better treatment planning of NPC. The significance of TSR has been studied in different types of epithelial malignancies including oral squamous cell carcinoma, 16 triple-negative breast cancer, 6 non–small cell lung cancer, 17 and urothelial carcinoma 7 . In NPC, one previous study has reported the significance of TSR based on a single institution cohort from an endemic region (China) 14 .…”
Section: Discussionmentioning
confidence: 99%